Peran Pengungkapan Aset Biologis dalam Memediasi Intensitas Aset Biologis dan Ukuran Perusahaan Terhadap Kinerja Perusahaan - Suhardjo, Iwan; Meiliana, Meiliana; Tryany, Julie; Erica, Erica; Arlina, Arlina; Jennifer, Jennifer (E-Jurnal Akuntansi, 2024)
This research aims to examine the influence of biological asset intensity and company size on company performance with biological asset disclosure as a mediating variable in agricultural companies on the Indonesia Stock Exchange for the 2017-2022 period. The research method used was a quantitative method and a sample of 16 companies was obtained. This research uses EViews as the main data analysis tool to support the validity and reliability of the findings. The results of this study show that (1) biological asset intensity and (2) company size have a positive effect on biological asset disclosure. (3) Disclosure of biological assets has a positive effect on company performance. (4) Disclosure of biological assets cannot mediate the relationship between biological asset intensity and company performance. (5) Disclosure of biological assets can mediate the relationship between company size and company performance. Keywords: Biological Asset Intensity; Biological Asset Disclosure; Firm Size; Firm Performance